Assistance in implementing the learning stage of school literacy movement at YBPK Christian Elementary School Malang - Melania Shinta Harendika; Aris Siswanti (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
YBPK Christian Elementary School in Ngaglik, Sukun, Malang has applied the School Literacy Movement (SLM) at the stages of habituation and development with the support from the Community Service Team, Faculty of Cultural Studies Universitas Brawijaya. The community service in 2021 was specifically aimed at assisting the school in implementing the SLM learning stage. At this stage, literacy activities were carried out in the pre-reading, whilst-reading, and post-reading activities. The post-reading activities resulted in several products, including mind maps, drawings, posters, and poems. The teachers observed that the students felt comfortable with the selected SLM activities. This also suggests that teachers are required to be resourceful in designing literacy activities. The programme evaluation reveals that some students were uninterested in the pre-reading activities because the teachers simply explained the vocabulary used in the reading. Nevertheless, the school is committed to keeping the SLM programme to help achieve the school goals of producing excellent graduates and creating an enjoyable learning atmosphere for the teachers and students.